ANALISIS DETERMINAN KINERJA PEGAWAI PADA RUMAH SAKIT UMUM DAERAH KABUPATEN SUMBAWA - Ahmad, Sari Usna Wita; Pamungkas, Binar Dwiyanto; Syafruddin, S (Samalewa: Jurnal Riset & Kajian Manajemen, 2023)
This study aims to analyze the the determinants of employee performance at the Regional General Hospital of Sumbawa Regency which consists of work quality (X1), work discipline (X2), and work ethic (X3). The type of this study was causal associative which aims to determine the influence or relationship between two or more variables. The data used in this study was quantitative data obtained directly from respondents using a questionnaire. The number of samples used as respondents in this study was 85 people who were selected using accidental sampling techniques. The data that has been collected was processed using the SPSS application to be studied using multiple linear regression analysis techniques, partial parameter hypothesis testing (t test), simultaneous parameter hypothesis testing (F test), and determinant coefficient test (R2). The results of this study showed that partially the work quality had a positive and significant effect on employee performance, meanwhile, work discipline and work ethic did not have effect on employee performance at the Regional General Hospital of Sumbawa Regency. Simultaneously, work quality, work discipline and work ethic had an effect on employee performance at the Regional General Hospital of Sumbawa Regency. Furthermore, the ability of work quality, work discipline and work ethic to influence changes in employee performance at the Regional General Hospital of Sumbawa Regency was very weak, namely 21.3%, so it is hoped that future research can use other variables not examined in this study, such as work competency, work motivation, leadership style, work environment, employee loyalty and commitment.